Celtic Pantheism in Coelho's Brida - Giri, Himal (Patan Prospective Journal, 2022)
This article investigates into pervasiveness of Celtic pantheism in Coelho’s Brida. Pantheism is a dominant theme in Celtic Christianity that is a modern form of Christian spirituality based in traditional belief structures and practices of the Celtic cultures of Britain and Ireland. The British religious studies scholar Marion Bowman Celtic spirituality defines Celtic Christianity that includes Celtic Christianity, and Celtic Paganism. While noting interrelations between other non-Christian forms, in this paper I mainly examine Celtic pantheism and analyze the interactions among the primary characters as portrayed in the novel.